Increasing Knowledge on the Prevention and Management of Anemia in Pregnant Women - Mulyani, Sri; Mutmainnah, Muthia; Meinarisa, Meinarisa; Jufira, Putry Rahmani; Salsabila, Silvi; Nabila, Tasya; Rifelda, Nadia; Amna, Etia Zaria; Usn, Tasya Isra Salsabila; Afrilia, Fadillah Nisa; Dewi , Eza Reiskha (Jurusan Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2024)
The prevalence of anemia sufferers in Indonesia is still relatively high. Efforts to prevent and treat anemia in pregnant women can include increasing knowledge. The aim of the service is to increase participants' knowledge about preventing and treating anemia in pregnant women. Community service was carried out at the Putri Ayu Community Health Center, Jambi City, targeting pregnant women who took part in pregnancy exercises. Extension activities begin with building a relationship of mutual trust and entering into a time contract. Next, counseling was carried out using power point media for presentations and leaflets were given at the end of the presentation session. The activity begins with an opening, delivery of material, evaluation with questions and answers and ends with a closing. Based on the evaluation results, it is known that all participants understand the material provided by the resource person and will try to implement it according to the material provided.